Ionic thermoelectric performance of cement and its modificationsFairdata (etsin) - Mostafa Yossef; Jukka Kuva; Seyedabolfazl Mousavihashemi; Andrew Ward; Marcus Perry; Tanja Kallio; Jari Puttonen (Case Studies in Construction Materials)
Ionic thermoelectric materials integrated into the concrete members of buildings have potential to generate electric energy utilizing thermal gradients. This paper investigates the effects of nickel foam (NF)-carbon nanotube (CNT) electrodes and the polyvinyl alcohol (PVA) hydrogel on the thermoelectric performance of hardened cement and evaluates the use of PVA as a charge carrier between the CNT electrodes and cement. The porosity of the cement samples was studied using micro-computed tomography. The results indicate that modifying the cement with PVA hydrogel increases capillary porosity while it reduces the Seebeck coefficient, overall strength, and capacitance. The increase of porosity observed to decrease the thermoelectric power. Pure cement samples without any modifications produced significant values up to 28 mV/K for the Seebeck coefficient, which can be explained by the diffusion of water inside the CNT nanochannels and its flow in cement microcracks and capillaries. These values pave the way for energy-efficient housing with increased grid independence.